2010
DOI: 10.1186/1750-9378-5-21
|View full text |Cite
|
Sign up to set email alerts
|

HLA polymorphisms and detection of kaposi sarcoma-associated herpesvirus DNA in saliva and peripheral blood among children and their mothers in the uganda sickle cell anemia KSHV Study

Abstract: Kaposi sarcoma-associated herpesvirus (KSHV, also called Human herpesvirus 8 or HHV8) is a γ-2 herpesvirus that causes Kaposi sarcoma. KSHV seroprevalence rates vary geographically with variable rates recorded in different sub Sahara African countries, suggesting that effects of genetic and/or environmental factors may influence the risk of infection. One study conducted in South Africa, where KSHV seroprevalence is relatively low, found that carriage of human leukocyte antigen (HLA) alleles HLA-A*6801, HLA-A*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
10
1
1
Order By: Relevance
“…However, we have previously reported that minority ethnicity was associated with higher KS risk in the same study, possibly suggesting that genetic traits rarer in minorities, ancestrally less exposed to the virus, may play a role in the immune responses to KSHV. We are currently investigating genetic risk factors for KSHV infection and KS in this case–control study; studies conducted in sub‐Saharan Africa reported some evidence of association between HLA polymorphisms and KSHV DNA detection in saliva and/or blood …”
Section: Discussionmentioning
confidence: 99%
“…However, we have previously reported that minority ethnicity was associated with higher KS risk in the same study, possibly suggesting that genetic traits rarer in minorities, ancestrally less exposed to the virus, may play a role in the immune responses to KSHV. We are currently investigating genetic risk factors for KSHV infection and KS in this case–control study; studies conducted in sub‐Saharan Africa reported some evidence of association between HLA polymorphisms and KSHV DNA detection in saliva and/or blood …”
Section: Discussionmentioning
confidence: 99%
“…The four most frequent Class II HLA alleles were: DPB1*04 , DRB1*15 , DPB1*01 , DPB1*03 and DPB1*02 ; DQA1*01 , DQA1*05 , DQA1*02 , and DQA1*03 ; HLA‐DQB1*06 , DQB1*05 , DQB1*03 , and DQB1*02 ; and HLA‐DRB1*13 , DRB1*15 , DRB1*01 , and DRB1*03 . The distribution of these alleles in the controls was comparable to the distribution reported in two other populations from Uganda (Guech‐Ongey et al , ) and Kenya (Peterson et al , ).…”
Section: Resultsunclassified
“…Through presenting a separate analysis of all mothers as well as KSHV‐infected mothers, the authors suggested that the three allele groups—A*68, A*43, and DRB1*04—might increase the likelihood of virus excretion rather than increasing susceptibility to infection with KSHV. However, in a study by Guech‐Ongey et al, the HLA‐A and HLA‐DRB1 alleles were not associated with KSHV shedding in children and their mothers in Uganda. The authors suggest that the contribution of individual HLA polymorphisms to KSHV shedding is important but may vary in different populations.…”
Section: Hla As a Component In Genetic Susceptibility To Kshv Infectimentioning
confidence: 87%